Polyherbal formulations for sustainable glycemic control in diabetes mellitus: phytochemical profiling, mechanistic insights, standardization and integration with conventional therapeutic approaches - Gupta, Abhilasha; Sharma, Arun (International Journal of Research in Medical Sciences, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by insulin resistance and pancreatic β-cell dysfunction persistent hyperglycemia, contributing to severe complications including cardiovascular, renal, hepatic, and neurological disorders. Worldwide incidence of diabetes has risen significantly, with over 537 million individuals affected in 2021, and projections indicate 783 million by 2045, imposing a significant public health and economic burden. Polyherbalism leverages synergistic interactions between multiple medicinal plants, enhancing therapeutic efficacy while minimizing toxicity. Commonly studied antidiabetic plants include Momordica charantia, Gymnema sylvestre, Trigonella foenum-graecum, Syzygium cumini, and Ocimum sanctum, which demonstrate hypoglycemic, antioxidant, and antihyperlipidemic activities by pathway like β-cell regeneration, decreased of glucose assimilation, and modulation of oxidative stress. This review highlights the potential of polyherbal formulations as safe, economically viable, and multi-targeted interventions for sustainable glycemic control, emphasizing the need for rigorous pharmacological, clinical, and formulation research to integrate traditional remedies into modern diabetes management.